A Case Study Power and Performance Improvement of a Chip Multiprocessor for Transaction Processing. - Ando, H.
Current high-end microprocessor designs focus on increasing instruction parallelism and clock frequency at the expense of power dissipation. This paper presents a case study of a different direction, a chip multiprocessor (CMP) with a smaller processor core than a baseline high-end 130-nm 64-bit SPARC server uniprocessor. We demonstrate that the size of the baseline processor core can be reduced by 2/3 using a combination of logical resource reduction and dense custom macros while still delivering about 70% of the TPC-C performance. Circuit speed is traded for power reduction by reducing the power supply from 1.0 to 0.8 V and increasing transistor channel lengths by 12.5% above the minimum. The resulting CMP with six reduced size cores and 4-MB L2 cache is estimated to run at 1.8 GHz while consuming less than 30% of the power compared to the scaled baseline dual-core processor running at 2.4 GHz. The proposed CMP is more than four times higher in TPC/W than the dual-core processor, facilitating the design of high-density servers.
Keywords: Chip multiprocessor; Dense custom macros; Logical resource reduction; Performance improvement; Power improvement; Transaction processing